THE EFFECTOF SPINNING WHEEL ON ADOLESCENT KNOWLEDGE AND ATTITUDES ABOUT PRE-MARITAL SEX IN BENGKULU CITY - Citra Syifa K.R; Yuniarti Yuniarti; Desi Widiyanti (IAKMI South Tangerang Branch, 2023)
Background: Adolescence is a time when everyone is curious about everything, including one sexual problem. Adolescents require sexual education instruction at this time in their personal development. Objective: The purpose of this study is to see how teaching using the Spinning Wheel affects adolescents' knowledge and attitudes toward premarital sex at SMA Negeri 10 in Bengkulu City. Method: This study employs a pre-experimental design with single-group pretest and posttest techniques. Proportionate stratified random sampling was performed with 40 class X students from SMA Negeri 10 Bengkulu City, and pre and post-questionnaires were employed for data collection. The analytical method uses the Wilcoxon test. Result: The results showed that there was an increase in the average knowledge of adolescents before (10.50) and after education (13,70) with a mean difference (3.2), an increase in the average attitude before (33.65) and after being given education (38.48) with a mean difference (4.83). There is an educational influence through the media Spinning Wheel On The increase in knowledge (P-Value=0,000) and attitudes (P-Value=0,000)of adolescents about premarital sex at SMA Negeri 10 Bengkulu City. Conclusion: There is an educational influence using Spinning Wheel media on teenagers' knowledge and attitudes about premarital sex. It is hoped that academics, educational institutions, and other researchers will use the Spinning Wheel media and develop android-based learning methods and other games to increase the knowledge and attitudes of adolescents, especially about premarital sex. Keyword: Teenagers, Premarital Sex, Spinning Wheel